(untitled) (International Journal of Biology and Chemistry, 2015)
Polysaccharides (PS) from wheat cell culture were isolated by liquid-liquid extraction. The molecular mass distribution was determined by gel-permeation chromatography (GPC) using dual detectors for the simultaneous detection. It was supposed that PS sample from wheat cell culture has molecular weight of 1632 Da. The physic-chemical properties of PS such as solubility in different solvents, surface activity, ξ-potential, the pH value, polydispersity (PDI) were determined. The PS sample was soluble in water and insoluble in ethanol, acetone and chloroform. ξ-potential of PS was evaluated in order to determine its charge at different pH value from 3 to 9. As a result, the ξ values for the PS solution were negative throughout the pH range studied, varying from -2.85 mV (pH 3.0) to -21.1 (pH 9). Using tensiometry method, surface tension of the PS at the liquid/air interface was investigated. At 0.05% concentration interfacial tension decreases slowly and reaches an equilibrium value after 8-8.5 hours. The pH was equal to 5.6±0.05. For a PS solution of 0.001% at pH 5.5 PDI was equal to 0.595.